A novel heterometallic [GdIII2MnII2] cluster displaying larger cryogenic magnetocaloric effect. (15th November 2020) - Zhang, Shen; Wang, Wen-Min; Guo, Yan; Li, Chao-Ying; Guo, Yu-Yu; Hou, Yin-Ling
Graphical abstract: A new and novel tetranuclear [Gd III 2 Mn II 2 ] cluster displays larger cryogenic magnetocaloric effect. Highlights: A [Gd III 2 Mn II 2 ] cluster was synthesized and structurally characterized. There was antiferromagnetic interaction in the [Gd III 2 Mn II 2 ] cluster. The [Gd III 2 Mn II 2 ] cluster displays well cryogenic magnetic refrigeration properties. Abstract: A 3d-4f cluster [Gd2 Mn2 (μ3 -OH)2 L4 (NO3 )4 ]·CH3 CN (1) (HL = methyl 3-methoxysalicylate) was synthesized successfully, the structure and magnetical property of 1 were characterized and discussed. Cluster 1 possesses two defective cubic-type tetranuclear core which were connected by two μ 3 -O and four μ 2 -O. In cluster 1, the Gd(III) ion is nine-coordinated and the Mn(II) is six-coordinated. The magnetic property research suggests that a weak antiferromagnetic interaction exists in cluster 1 . It is important that cluster 1 exhibits larger cryogenic magnetocaloric effect with a maximum -Δ S m of 40.59 J kg −1 K −1 for Δ H  = 7 T at 2.0 K.